2014
DOI: 10.1136/bcr-2013-203085
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral cryptorchidism with bilateral synchronous abdominal testicular germ cell tumour

Abstract: SUMMARYCryptorchidism or undescended testis is a very common anomaly of the male genitourinary system. It is one of the established risk factors for testicular tumour. The commonest malignancy noted in cryptorchidism is seminoma testis. The presence of bilateral abdominal synchronous testicular tumour in cryptorchidism is very rare. BACKGROUND

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…Our prior studies have demonstrated that senescence markers can be useful in the diagnosis of cryptorchidism in mixed-breed dogs [39]. In horses, as in dogs or humans, testis/testes located in the abdominal cavity can result in neoplasm development [40,41]. Here, for the first time, biochemical staining for protein, acid, and polysaccharide content in healthy and cryptorchid horse testes was performed.…”
Section: Discussionmentioning
confidence: 97%
“…Our prior studies have demonstrated that senescence markers can be useful in the diagnosis of cryptorchidism in mixed-breed dogs [39]. In horses, as in dogs or humans, testis/testes located in the abdominal cavity can result in neoplasm development [40,41]. Here, for the first time, biochemical staining for protein, acid, and polysaccharide content in healthy and cryptorchid horse testes was performed.…”
Section: Discussionmentioning
confidence: 97%
“…Refining the PubMed search further, using the terms "bilateral," "adult," "cryptorchidism," "orchidopexy," and "orchiectomy," 35 articles were found. After excluding articles in non-English languages, those that were published over 10 years ago, and those that reported on unilateral cryptorchid cases, pediatric cases, specific surgical techniques, or articles that were irrelevant, five articles were selected and reviewed [10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…During the review, the age of surgical intervention, type of surgical intervention (orchidopexy vs. orchidectomy), associated infertility, associated neoplasms, and any other associated abnormality were noted. Of the articles reviewed, there were 10 case reports of adult bilateral cryptorchidism, with an average age of diagnosis and intervention at 31.8 years [3][4][5][6][7][8][9][11][12][13]. Three of the 10 individuals underwent orchidopexy, five individuals underwent orchidectomy, and two underwent orchidopexy on one side with orchidectomy on the other [3][4][5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations